Godsbeelde in die liturgie - Vos, Casparus Johannes Adam (HTS teologiese studies, 2010)
Images of God in the liturgy In this article, the research hypothesis is that a one-sided liturgy leads to a watered-down image of God. When room for God is not created in the liturgy, God is not encountered in all God’s glory. As a result, worshippers cannot fully bring homage to God’s glory. From this perspective, the article explores the different faces of God in the liturgy. These diverse images of God lead to a rich diversity of views and experiences of God by worshippers.